Analisis Finansial Pola Tanam Agroforestri di Desa Pesawaran Indah Kecamatan Padang Cermin Kabupaten Pesawaran Provinsi Lampung - Nurpine Nadeak; Rommy Qurniati; Wahyu Hidayat (Jurnal Sylva Lestari, 2013)
Agroforestry in Indonesian language simply means as planting trees on agricultural land. Land's management with sustainable agroforestry systems expected to be able improve field productivity. It has needed to do financial analysis for agroforestry cropping patterns. It based on some of dominant plant species in agroforestry cropping patterns. This study conducted in the Pesawaran Indah Village of Padang Cermin Subdistrict on Pesawaran District in March-May 2012. The study aims to determine a profitable agroforestry cropping patterns based on financial analysis. Sampling used by purposive sampling technique. Financial analysis of agroforestry cropping pattern used the NPV, BCR and IRR with feasibility age of 20 years and an interest rate of 12%.The results showed that there are 9 agroforestry cropping patterns applied. Analysis showed that agroforestry cropping patterns is financially viable to be applied. Among 9 cropping pattern, pattern VI which is combination of Cocoa, Coconut and Banana has the highest profit with NPV is Rp 71.392.802,34,-, BCR of 7,39 and an IRR of 96%. Key words : agroforestry, financial analysis, pattern